The Impact of Text to Speech Software on Pronounciation for Students Senior High School - Silvia Qorunnada; Abd. Aziz Wahab; Shofiatul Hasanah (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstrak Penelitian ini berjutuan untuk mengetahui pengaruh ucapan siswa melalui software text-to-specch ini dikembangkan di electrotechnical laboratiry, jepang pada tahun 1968. Penelitian inin menggunakan penelitian kuantitatif. Ini terdiri dari tiga langkah, yaitu pre-test, treatment, dan post-test. Subjek penelitian ini adalah seluruh siswa kelas x sirojut thalibin senior high school. Tesnya adalah pengucapan kata yang terdiri dari 20 kata pre-test dan post-test. Temuan penelitian menunjukkan bahwa text-to-speech signifikan dalam meningkatkan pengucapan siswa. Hal ini dibuktikan dengan skor rata-rata sebelumnya adalah 49,33 dan skor rata-rata setelah diberikan perlakuan adalah 78,67. Presentase peningkatannya adalah 59.47%. Artinya ada peningkatan terhadap pengucapan siswa. Kata Kunci: Perangkat Lunak Text-To-Speech, Pengucapan, Diphtong Abstract The purpose of this research is to find out the effect of the student's pronunciation using text-to-speech software. This software was developed in an electrotechnical laboratory in Japan in 1968. This study used quantitative research. It consisted of wooden stairs for pre-, treatment and post-testing. The subjects of this study were all x scattered students of Thalib High School. The test was a spoken word consisting of 20 words for a pretest and a posttest. The result of the study showed that the text-to-speech function is important to improve students' pronunciation. This was demonstrated by the mean score before treatment 9.33 and after treatment 78.67. The recovery rate was 59. 7%. This means that the student's pronunciation will improve. Keywords: Speech Conversion Software, Pronunciation, Diphthong